Relación de calidad de cuerpo lúteo con características uterinas y niveles de progesterona en D5 post – ovulación, en yeguas - Mocha Brito, Adriana Nathaly (2023)
The corpus luteum (CL) does not always result in a homogeneous structure, it can be cavitary, therefore it is important to study its morpho-echogenicity and function. The objective of this study was to relate the quality of the CL with progesterone levels (P4) and uterine characteristics on day 5 post-ovulation in mares. Ten cyclic mares were used, follicular development was monitored until ovulation (D0), and on D5, ultrasound images of the uterus were taken at four points, 3 videos of the CL, and blood samples (serum). The selected images were analyzed by the Image J program, using histograms (pixels). Statistical analysis was performed using PROC MIXED and PROC CORR models (SAS, 2023). Non-cavitary CL presented greater (p<0.05) minimum and mode of pixels than cavitary CL, however, there was no difference in the mean pixels or in the maximum value. Cavitary CLs presented greater (p<0.05) total area, cavitary area, perimeter and diameter than non-cavitary CLs, while there was no difference in the integral area, however, at P4 levels, there was no statistical difference. There was a side effect, where left CL presented greater (p<0.05) total area, integral area, perimeter and diameter than right CL, although there was no difference in cavitary area. The echogenicity of the CL positively influenced the echogenicity of the uterus, being that the maximum pixel value was higher (p=0.01) at the base than at the tip of the uterine horn. Mares with intact CL presented higher (p<0.005) uterine tone than with cavitary CL, and there was no difference in cervical tone and edema. At D5 post-ovulation, the morpho-echogenicity and dimensions of the mare's CL did not interfere on P4 levels, but they did on uterine tone.